ACTIVE MEDIA : Experimental results on the dissociation of molecular iodine in the presence of singlet oxygen molecules. (31st August 2016) - Zagidullin, M V; Khvatov, N A; Malyshev, M S; Svistun, M I
Abstract: The experimental results on the dissociation of iodine molecules in the presence of single oxygen molecules under a widerange variation of the oxygen–iodine composition are presented. The rate constants are determined as 4.3 × 10 -17 cm 3 s -1 for the reaction O2 ( 1 Δ) + O2 ( 1 Δ) → O2 ( 1 Σ) + O2 ( 3 Σ) (reaction 1), 2.8 × 10 -13 cm 3 s -1 for the reaction O2 ( 1 Δ) + I( 2 P1/2 ) → O2 ( 1 Σ) + I( 2 P3/2 ) (4) and 8.3 × 10 -11 cm 3 s -1 for the reaction O2 ( 1 Σ) + I2 → O2 ( 3 Σ) + 2I (2). The analysis of the experimental results shows that for different compositions of the active medium of the oxygen–iodine laser the iodine dissociation occurs via the chain of reactions 1, 2, O2 ( 1 Δ) + I( 2 P3/2 ) → O2 ( 3 Σ) + I( 2 P1/2 ), 4 and in the cascade process I2 + I( 2 P1/2 ) → I2 (u) + I( 2 P3/2 ), I2 (u) + O2 ( 1 Δ) → 2I + O2 ( 3 Σ). For typical active medium compositions of the supersonic chemical oxygen–iodine laser, the contributions of each of the mechanisms to the dissociation are comparable. The experiments carried out did not reveal any contribution from the vibrationally excited oxygen molecules to the iodine dissociation. Thus, the performed experiments and the conclusions drawn from them completely confirm the mechanism of iodine dissociation, proposed earlier.